ASSESSMENT ON PREVALENCE OF HYPERTENSION AND ITS ASSOCIATED RISK FACTORS ALONG WITH MMAS SCORE IN A RURAL COMMUNITY: A HOME BASED SCREENING - Kandasamy, Krishnaveni; Rajagopal, Shanmuga Sundaram; Ramalingam, Kameswaran; Krishnan, Karthikeyan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: In India, a study on hypertension (HTN) prevalence conducted in a community over a period of 3â€“6 decades showed an increase of 30% in urban population and 10% in rural population. The study aimed to assess the prevalence of HTN and pre-HTN in a rural community and also to find the significance of risk factors which precipitate to it. Methods: This cross-sectional study was conducted in a rural community of Salem district, Tamil Nadu, India. HTN and pre-HTN was defined by the Joint National Committee 8th report guidelines. Patient data’s (sociodemographic variables, lifestyle factors, and medical reports) were collected with the help of questionnaire. Identified hypertensive patients were assessed with MMAS-8 questionnaire. Results: During the study period of 8 months, 425 subjects were screened and studied for HTN and pre-HTN. More than half (69.4%) of the study group were found to be hypertensive. Of the 295 reported cases, 228 (53.6% of 425) were knownâ€ cases of HTN and 67 (15.8% of 425) were newly diagnosed cases. A positive association (p<0.05) was observed between HTN and age, body mass index (BMI), alcohol, and tobacco use other than smoking. 75 patients were found to be prehypertensive, in that 57.3% (43 cases) were male and 42.7% (32 cases) were female. Majority of hypertension patients (66%) were with low adherence than 24% medium and 10% high adherence towards their medications. Conclusion: Our study concluded that the prevalence of pre-HTN and HTN was higher among the study population, so there is a need for screening of individuals at the early age group. Further studies are needed to observe and confiscate the reasons why majority of hypertensive patients with low medication adherence.